2018
DOI: 10.1371/journal.pone.0190898
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a LED flashlight technique in reducing livestock depredation by lions (Panthera leo) around Nairobi National Park, Kenya

Abstract: The global lion (Panthera leo) population decline is partly a result of retaliatory killing in response to livestock depredation. Nairobi National Park (NNP) is a small protected area in Kenya surrounded by a human-dominated landscape. Communities around the park use flashlights to deter lions from their livestock bomas. We investigated the response by lions to the installation of a LED flashlight technique during 2007–2016.We interviewed 80 owners of livestock bomas with flashlights (n = 43) and without (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 40 publications
2
28
1
Order By: Relevance
“…Improving condition of animal enclosures, use of livestock guardians (herders and trained dogs), visual, auditory deterrents and lethal control of predators have been identified as the major interventions which have effectively reduced livestock losses ( Van Eeden et al, 2018 ; Miller, Jhala & Schmitz, 2016 ; Eklund et al, 2017 ). Light based deterrents have been documented to effectively protect livestock against lions ( Panthera leo ) ( Lesilau et al, 2018 ) and pumas ( Ohrens, Bonacic & Treves, 2019 ) and our results also support such findings. However, not all visual deterrents are effective, e.g., scarecrows and lion lights have failed to prevent livestock losses to leopard attacks in east Africa ( Broekhuis, Cushman & Elliot, 2017 ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Improving condition of animal enclosures, use of livestock guardians (herders and trained dogs), visual, auditory deterrents and lethal control of predators have been identified as the major interventions which have effectively reduced livestock losses ( Van Eeden et al, 2018 ; Miller, Jhala & Schmitz, 2016 ; Eklund et al, 2017 ). Light based deterrents have been documented to effectively protect livestock against lions ( Panthera leo ) ( Lesilau et al, 2018 ) and pumas ( Ohrens, Bonacic & Treves, 2019 ) and our results also support such findings. However, not all visual deterrents are effective, e.g., scarecrows and lion lights have failed to prevent livestock losses to leopard attacks in east Africa ( Broekhuis, Cushman & Elliot, 2017 ).…”
Section: Discussionsupporting
confidence: 89%
“…Radio-telemetry studies in Nepal and India have documented leopards to be nocturnal (Odden & Wegge, 2005;Odden et al, 2014) but our results suggest diurnal activity peaks within human dominated mountainous landscapes. Cheetahs and lions in eastern Africa (Broekhuis et al, 2014;Lesilau et al, 2018) and tigers in Sundarban delta (Naha et al, 2016) have also been reported to exhibit diurnal activity peaks and are believed to be the major driver of human-carnivore conflicts. Leopards probably prefer to kill wild prey at night whereas livestock killing is diurnal due to the availability, poor or unsupervised grazing practices, and ease of catching domestic prey.…”
Section: Discussionmentioning
confidence: 99%
“…Deterrents that mimic human presence, such as noise or lighting (e.g., Foxlights [Foxlights International, Australia]), can produce a perception of greater risks for carnivores (Lesilau et al. 2018). By increasing the costs, real or perceived, of preying on livestock, a livestock manager can create suboptimal conditions for predation and prompt a carnivore to switch to other, less costly alternatives.…”
Section: Ecological Mechanisms Of Livestock Predationmentioning
confidence: 99%
“…This was a result of different effects of interventions on different predators. Visual deterrents varied from very effective flashlights against lions (Lesilau et al, 2018) to ineffective scarecrows against leopards (Woodroffe et al, 2007). Herding was very effective by adult men (Ciucci & Boitani, 1998) and highly ineffective by children (Tumenta et al, 2013;Woodroffe et al, 2007).…”
Section: Discussionmentioning
confidence: 99%